Some variables involved in the development of foster care contact visits in Andalusia - González-Pasarín, Lucía; Bernedo-Muñoz, Isabel María (My University, 2021)
It has been argued that contact visits between foster children and birth parents can help maintain attachment bonds and support the child’s development. The main aim of this study is to analyse the characteristics of contact visits between non-kinship foster children and their birth parents in Andalusia. This study was funded by the research project Application of a psychoeducational intervention program to improve visits between foster children and their biological families (EDU2016 77094-P). Participants were 212 non-kinship foster children and their respective birth families. We conducted frequency and non-parametric analysis of features of contact visits collected by the Child File Summary Form designed for this study. The results show that the main visitor is the mother; the frequency of the majority of visits is monthly; and most of them are supervised. Furthermore, there are significant differences between the development of visits and the following variables: attendance regularity, contact visits frequency, supervised contact and number of extended family who visits. By contrast, there are not significant differences with the number of main visitors and if they are from the birth family. Results highlight some variables that could be involved in the quality of contact visits. The implication for the practice of this study is to develop intervention strategies targeted at all those involved (foster child, birth family, foster family and social workers).
Keywords: Tutela; Foster care; Contac visit; Birth parent